Properties of Solutions to Fractional Laplace Equation with Singular Term (Journal of Partial Differential Equations, 2023)
The aim of the paper is to study the properties of positive classical solutionsto the fractional Laplace equation with the singular term. Using the extension method,we prove the nonexistence and symmetric of solutions to the singular fractional equation.
Keywords: Fractional Laplace equation; extension method; method of moving planes; symmetry.